Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages THE LABOUR PARTY Reports on HOSPITALS AND THE PATIENT and a DOMESTIC WORKERS' CHARTER To be presented by the Standing Joint Committee of Industrial Women's Organisations to the NATIONAL CONFERENCE OF LABOUR WOMEN, BLACKPOOL June 2, 3, and 4, 1931 Price 1d. Post Free 1½d. 1s. per dozen These Reports will also be issued to Delegates with their credentials and the Final Agenda. Published by the Labour Party, Transport House, Smith Square, London, S.W.1. 126/TG/RES/X/1036A/7